2021
DOI: 10.1186/s12885-021-08895-1
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of circSMAD2 inhibits the tumorigenesis of gallbladder cancer through binding with eIF4A3

Abstract: Background Gallbladder cancer (GBC) is the seventh most common gastrointestinal cancer worldwide. This study aimed to investigate the function of circSMAD2 in GBC. Methods To investigate the function of circSMAD2 in GBC, the level of circSMAD2 in GBC cells was detected by RT-qPCR. CCK-8 assay was performed to investigate the cell viability. Cell apoptosis was tested by flow cytometry. In addition, transwell assay was used to detect the cell migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…FOXP1 enhances GBC progression via PKLR signaling [ 25 ], and circRNAs are involved in the promotion of GBC. Researchers have suggested that inhibition of circRNA SMAD2 suppresses the growth of GBC through eIF4A3 [ 26 ]. However, there are few reports on the role of the circRNA NGFR in GBC development.…”
Section: Discussionmentioning
confidence: 99%
“…FOXP1 enhances GBC progression via PKLR signaling [ 25 ], and circRNAs are involved in the promotion of GBC. Researchers have suggested that inhibition of circRNA SMAD2 suppresses the growth of GBC through eIF4A3 [ 26 ]. However, there are few reports on the role of the circRNA NGFR in GBC development.…”
Section: Discussionmentioning
confidence: 99%
“…13 Additional research showed that circSMAD2 can inhibit the binding of eukaryotic translation initiation factor 4A3 (EIF4A3) to SMAD2 by binding to EIF4A3, thereby affecting the progression of gallbladder cancer. 14 Yuan et al found that hsa_circ_0072309 promotes autophagy among glioblastoma cells and increases their sensitivity to temozolomide through a P53-dependent mechanism. 15 Furthermore, circRNAs have been used to help diagnose disease based on liquid biopsies of tumors.…”
Section: Circrna S and D Is E A S Ementioning
confidence: 99%
“…Down‐regulation of circRNA_010383 promotes the accumulation of extracellular matrix (ECM) proteins, promoting proteinuria, and renal fibrosis in patients with diabetic nephropathy, and can be used as a therapeutic target for diabetic nephropathy 13 . Additional research showed that circSMAD2 can inhibit the binding of eukaryotic translation initiation factor 4A3 (EIF4A3) to SMAD2 by binding to EIF4A3, thereby affecting the progression of gallbladder cancer 14 . Yuan et al.…”
Section: Circrnas and Diseasementioning
confidence: 99%